Fluazuron-induced morphological changes in Rhipicephalus sanguineus Latreille, 1806 (Acari: Ixodidae) nymphs: An ultra-structural evaluation of the cuticle formation and digestive processes - Oliveira, Patricia Rosa de [UNESP]; Calligaris, Izabela Braggiao [UNESP]; Nunes, Pablo Henrique [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Elsevier B.V., 2014)
Rhipicephalus sanguineus is a species of tick which is widely distributed in America, Africa and Australia and is probably the most prevalent among all the other ixodid tick species. The present study demonstrated the effects of the arthropod growth regulator fluazuron (Acatale((R))), in the formation of the integument and the digestive processes of R. sanguineus nymphs fed on rabbits treated with different doses of this chemical acaricide. For this, three different doses of fluazuron (20 mg/kg, 40 mg/kg and 80 mg/kg) were applied pouron to the hosts divided into three different treated-groups (II, III, IV) of three animals each. A fourth group (I) of rabbits (n = 3) was given distilled water as control. On the first day after treatment (24 h), the hosts were artificially infested with R. sanguineus nymphs. After full engorgement (7 days), the nymphs were removed and placed on labeled Petri dishes and kept in BOD incubator for 7 days. The engorged nymphs were then taken to ultra-structural analysis. Results revealed the following main ultra-structural changes in the nymphs integument and midgut of the different treated groups (II, III, IV): cuticle disorganization and the absence of subdivisions, damages in the integument epithelial cells, size of digestive cells, amount of endosomes, autophagic and digestive vacuoles, accumulated digestive residues, lipid droplets and organelles found in the digestive cells' cytoplasm, as well as the presence of microvilli in their plasma membranes. It is concluded that fluazuron may act on the integument and midgut cells of R. sanguineus engorged nymphs by impairing the synthesis of the new cuticle and the digestive processes (absorption of the blood ingested from the host, digestion - hemolysis, formation of digestive residues and release of nutrients to be converted into lipid, as well as for the synthesis of structural protein), which interfere in the development of nymphs, being able to prevent the emergence of adults after periodical ecdysis. These data indicate the possibility to use this arthropod growth regulator (AGR) in the control of R. sanguineus, at least in the nymphal stage of its biological cycle. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Fluazuron; Cuticle; Acaricide; Nymphs; Control; Ultrastructure